The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2196/jmir.2816
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Flexibility in Mobile Health: Lessons From a Government-Sponsored Home Care Program

Abstract: BackgroundMobile technologies have emerged as important tools that health care personnel can use to gain easy access to client data anywhere. This is particularly useful for nurses and care workers in home health care as they provide services to clients in many different settings. Although a growing body of evidence supports the use of mobile technologies, the diverse implications of mobile health have yet to be fully documented.ObjectiveOur objective was to examine a large-scale government-sponsored mobile he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 54 publications
2
36
0
1
Order By: Relevance
“…Client management features: scheduling [ 75 ], patient record/information access [ 64 , 72 , 83 ], voice and text messaging [ 64 , 73 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Client management features: scheduling [ 75 ], patient record/information access [ 64 , 72 , 83 ], voice and text messaging [ 64 , 73 ]…”
Section: Resultsmentioning
confidence: 99%
“…The process of adoption and diffusion of an mHealth solution was reported in a case review from Denmark [ 72 ]. Adoption of telehealth for community-dwelling older adults at a national level was reportedly triggered by demonstrated successes of a municipal project that simultaneously met the interests of major government stakeholders looking for fiscal efficiencies in health care delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation is uncertainty about whether mHealth solutions can meet expectations of saving time and maintaining high-quality care, and thus have an added value in delivering health services. Building end-user trust in mHealth solutions, preferably by providing evidence-based information on app credibility, is an important enabler to increase promotion of mHealth solutions by GPs (45,52,53). This includes information on perceived usefulness, ease of use, risks associated with accessing and communicating personal health data and a measure of trust in the developers of the mHealth technologies (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…A second strategy is for the government or health insurer to provide incentives for pioneers to make mHealth adoption more attractive. Several studies found strong stakeholder collaboration in which financial support is assured to initiate and energize the mHealth adoption process (47,52,57). A crucial facilitator is therefore to create collaborative platforms including key stakeholders, such as end-users, health insurers and industry players to make a sound business case shaping the adoption process.…”
Section: Discussionmentioning
confidence: 99%
“…A pitfall of such a development approach is that it might become 'messy' because many different types of data are collected and results can be conflicting. In order to structure the development and decision-making process, a multidisciplinary project team coordinated the project, which is in line with recommendations on eHealth development [3,28,36,37]. Also, to deal with the large amounts of data, this project's approach consisted of systematic and structured research activities.…”
Section: Discussionmentioning
confidence: 99%